Combining Bioinformatics Techniques to Study the Key Immune-Related Genes in Abdominal Aortic Aneurysm - Nie, Han; Qiu, Jiacong; Wen, Si; Zhou, Weimin (Frontiers in Genetics, 2020)
Approximately 13,000 people die of abdominal aortic aneurysm (AAA) every year. This study aimed to identify immune-response-related genes that play important roles in AAA using bioinformatics approaches. We downloaded the GSE57691 and GSE98278 datasets related to AAA from the Gene Expression Omnibus database, which included 80 AAA and 10 normal vascular samples. CIBERSORT was used to analyze the samples and detect the infiltration of 22 types of immune cells: their differences and correlations. Principal component analysis showed that there were significant differences in the infiltration of immune cells between normal vascular and AAA samples. High proportions of CD4+ T cells, activated mast cells, resting natural killer cells, and 12 other types of immune cells were found in normal vascular tissue, whereas high proportions of macrophages, CD8+ T cells, resting mast cells, and 6 other types of immune cells were found in AAA tissue. In the selected samples, we identified 39 upregulated (involved in growth factor activity, hormone receptor binding, and cytokine receptor activity) and 133 downregulated genes (involved in T cell activation, cell chemotaxis, and regulation of immune response mediators). The key differentially expressed immune-response-related genes were screened using the STRING database and Cytoscape software. Two downregulated genes, PI3 and MAP2K1, and three upregulated genes, SSTR1, GPER1, and CCR10, were identified by constructing a protein-protein interaction network. The functional enrichment of the differentially expressed genes was analyzed, and the expression of the five key genes in AAA samples was verified by quantitative polymerase chain reaction, which revealed that MAP2K1 was downregulated in AAA, whereas SSTR1, GEPR1, and CCR10 were upregulated in AAA; there was no significant difference in PI3 expression. Our study shows that normal vascular and AAA samples can be distinguished by the infiltration of immune cells. Five genes, PI3, MAP2K1, SSTR1, GPER1, and CCR10, may play important roles in the development of AAA and help diagnose and treat AAA.